Performance improvement of rectifiers for WPT exploiting thermal energy harvesting. Issue 1 (13th April 2015) - Virili, Marco; Georgiadis, Apostolos; Collado, Ana; Niotaki, Kyriaki; Mezzanotte, Paolo; Roselli, Luca; Alimenti, Federico; Carvalho, Nuno B.
Abstract : This paper proposes a combined harvesting system to improve the efficiency and flexibility of autonomous wireless network nodes, supplied by means of wireless power transfer technique. In particular, a mixed system for electromagnetic (EM) and thermal energy harvesting (EH), conceived for passive nodes of wireless sensor networks and radio frequency (RF) identification tags, is described. The proposed system aims at increasing the effectiveness and the efficiency of the EH system by integrating an antenna and a rectifier with a thermo-electric generator (TEG) able to perform thermal EH. The energy provided by the thermal harvester is exploited twice: to increase the rectifier efficiency by providing a voltage usable to improve the bias condition of the rectifying diode, and to provide additional dc energy, harvested for free. Ultimately, a great efficiency improvement, especially at low incident RF power, has been observed. The design methodology and the EM performance of a quarter-wavelength patch antenna, integrated with the TEG are resumed. Then, a test campaign to evaluate the thermal EH performance has been carried out. Afterward, a rectifier with variable bias voltage, operating at the same frequency of the antenna, has been opportunely designed to exploit the harvested thermal energy to bias the diode. A measurement campaign has been then carried out to test the efficiency increment obtained and to validate the proposed solution.